Geography vs. Institutions at the Village Level - Michael Grimm; Stephan Klasen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
There is well-known debate about the respective role of geography versus institutions in explaining the long term development of countries. These debates have usually been based on cross country regressions where questions about parameter heterogeneity, unobserved heterogeneity, and endogeneity cannot easily be controlled for. The innovation of Acemoglu, Johnson and Robinson (2001) was to address this last point by using settler morality as an instrument for endegenous institutions and found that this supported their line of reasoning. We believe there is value-added to consider this debate at the micro level within a country as particularly questions of parameter heterogeneity and unobserved heterogeneity are likely to be smaller than between countries. Hence, we examine the determinants of agricultural growth across villages on the Indonesian Island of Sulawesi and find technology adoption to play a crucial role. We show that geography through its effects on migration and institutions is a valid instrument to establish the causal links between institutions and technology adoption as well as technology and agricultural growth.
Keywords: Q12; O12; K11; 330; Geography; land rights; migration; technology adoption; agricultural developement; Indonesia